Comparison of Complications of Postpartum Iucd (Ppiucd) Insertion with Interval Iucd Insertion - Munazzah Bashir, Shazia Ashraf, Mehreen Khalil Qureshi, Syeda Sana Ali, Mahvesh Mahmud, Lamia Yusuf, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: Present study was aimed to compare complications of postpartum IUCD insertion with interval IUCD insertion. Study design: Retrospective study Place and duration: Conducted at Gynae & Obs, AIMC/Jinnah Hospital Lahore during from August 2021 to March 2022. Methods: 110 women who used IUCDs were enrolled in this study. They all were equally divided into two groups (PPIUCD group and Interval IUCD group). Women ages were ranging from 20 to 35years. Patients detailed medical history including age, residence, socioeconomic status were examined after taking written consent. Outcomes were examined at follow-up and compared between both groups. Patients with Chorioamnionitis, Puerperal sepsis, PROM > 18 hrs, Potentially infected dai handling cases, Unresolved PPH were excluded from the study. Data was analyzed by SPSS 20.0. P-value <0.05 was considered as significant. Results: Out of 110 patients of accepted IUCD, most of the patients were aged between 20 to 30 years who had used intrauterine contraceptive device and comprised 77.3%. Women with PPIUCDs had low complication rate as it was reported in 13 cases (23.47%) while (27.19%) was reported in 15 cases of Interval IUCDs group. Pregnancy and perforation was 0%. 48 (87.3%) women were satisfied with their PPIUCDs whereas 45 (81.8%) were satisfied with their Interval IUCDs. Continuation rate with PPIUCD was high 49 (89.1%). Bleeding problem was significantly higher in women with Interval IUCD (9.09%). Women with PPIUCD had more expulsion rate (7.27%). Rate of removal of IUCD in both the groups had minimum difference (9.09% and 10.9%). Conclusion: It is concluded that the insertion of immediate postpartum intrauterine contraceptive devices was effective and safe method with low complications rate. Keywords: PPIUCD, Interval IUCD, complications